Pemanfaatan Aplikasi “TBMenu” untuk Penderita Tuberkulosis di Kota Medan - Humairah Medina Liza Lubis; Fitri Nur Malini; Emni Purwoningsih (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Malnutrition and tuberculosis are common problems in most developing and underdeveloped countries, including Indonesia. These two problems tend to interact with each other. Significantly lower nutritional status was found in patients with active tuberculosis (TB) compared to healthy people. Malnutrition can lead to the secondary immune deficiency that increases the host's susceptibility to infection. In patients with tuberculosis, malnutrition can cause decreased appetite, malabsorption of nutrients, micronutrient malabsorption, and metabolic changes that are detrimental to the patient. Protein-energy malnutrition and micronutrient deficiencies increase the risk of tuberculosis. In malnourished patients, the healing process is relatively longer and the mortality rate is higher than in well-nourished patients. Knowledge of good nutrition and also economic status also affects the severity of tuberculosis. Partner problems that can be identified are as follows: (1) Increasing TB cases from day to day, (2) Low cure rates for TB patients, (3) Finding cases of death due to TB, (4) Finding cases of malnutrition and tuberculosis, Solutions to problems offered to solve the problems faced by partners are as follows: (1) Adequate counseling and debriefing to assist TB patients to achieve high cure rates. (2) Designing the “TBMenu” application program which introduces an android-based application about simple, inexpensive and useful nutrition options for TB patients with middle to lower economies. This application is made based on body weight, the length of treatment the patient has been on. In addition, it can also assess the nutritional status of patients in order to measure and control tuberculosis in the city of Medan. Health education and debriefing about the dangers of TB has been carried out to 20 TB patients at the Exemplary Health Center in Medan Kota District through a zoom meeting due to limitations due to the Covid-19 pandemic